Targeting visceral leishmaniasis by mannosylated liposome incorporated pitc-2 isolated from the plant pluchea indica (L) less. - SHARMILY CHAKRABORTY; TAPAN KUMAR CHATTERJEE (International Journal of Pharma and Bio Sciences, 2017)
Leishmaniasis is a vector borne disease, endemic in large populated areas. PITC-2 is a natural compound, isolated from evergreen herb Pluchea indica(L.) Less. Animal studies have revealed that PITC-2 is non-toxic. The primary objective of this study was to demonstrate the possible increase in efficacy of mannosylated derivatives of PITC-2 in leishmania infected hamsters. The efficiencies of intercalated and mannose grafted liposomes of PITC-2 were found to be 37.24% and 31.25%, respectively, with the molar ratio of phosphatidylcholine, cholesterol and PITC-2 being 9:1:1. In in vitro studies liposomes in excised rat skin indicated slow release and penetration of PITC-2 liposomes. PITC-2 showed a significant anti-leishmanial activity against promastigotes (extracellular) of parasite Leishmania donovani in vitro. The IC50 of PITC-2 was 1.095 µg. The efficacies o f PITC-2 liposomes were tested against experimental leishmaniasis in mice and hamster models in three different forms: free PITC-2, Liposome intercalated and mannose grafted liposome of PITC-2. Efficacy of PITC-2 was significantly improved with mannose grafted liposome, as demonstrated by 88.30 % (in mice model) and 84.27% (in hamster model) reduction of splenic parasitic burden, respectively and 74.81% (in mice model) and 80.21% (in hamster model) reduction of liver parasitic burden, respectively. Histology of spleen and selected liver function tests (Alkaline phosphatase, SGPT and SGOT in blood plasma) indicated that the toxicity of PITC-2 was comparable to controls in mannosylated liposome incorporated PITC-2 animals. Although the drug release profile did not differ much the mannose grafted PITC-2 encapsulated liposomes were found to be effective in significantly lowering splenic and liver parasitic loads without toxicity.